Survey of knowledge, practice, and associated factors toward home management of childhood fever among parents visiting Gondar health facilities in 2022 - Assimamaw, Nega Tezera; Gonete, Almaz Tefera; Terefe, Bewuketu (Frontiers in Pediatrics, 2024)
Background Fever is a typical symptom of many sicknesses, but for children under the age of five, fever can have devastating consequences and represents a source of worry for parents. To the best of our knowledge, no research on home management of fever in children has been conducted in Ethiopia. We aimed to assess knowledge, practices, and associated factors towards home management of childhood fever among parents visiting Gondar Town health facilities in 2022. Method This multicenter institutional-based cross-sectional study was conducted in Gondar public health facilities from June 1st—June 30th, 2022. Participants were fathers and mothers of children aged 0–5 years. A stratified random sampling technique was used. Data were collected through face–to–face interviews using a pretested structured questionnaire. Results Approximately, 40.2% (95% CI: 35.5%, 45.2%) of parents had good knowledge and only 12.8% (95% CI: 9.7–15.8) of parents practiced home fever management. Being married [Adjusted odds ratio [(AOR) = 2.1 (1.2, 3.2)], having a primary or higher level of education [AOR = 2.4 (1.17, 4.9)] [AOR = 2.0 (1.02–4.6)], respectively, and number of children [AOR = 1.8 (1.63, 2.03)] were factors associated with parental knowledge. Likewise, being married [AOR = 3.05 (2.27.50–3.83)], receiving counseling from health care providers [AOR = 2.12 (1.53–3.32)], and being male [AOR = 2.03 (1.50–3.00)] were significant predictors of practice. Conclusion Inadequate levels of knowledge and numerous irrational practices related to home fever management were predominant among parents, which needs to be addressed. Evidence-based health education is essential for parents to enhance their level of knowledge and practice to effectively treat fever at home.